2021
DOI: 10.11591/ijpeds.v12.i3.pp1751-1763
|View full text |Cite
|
Sign up to set email alerts
|

A modified bridge-type nonsuperconducting fault current limiter for distribution network application

Abstract: The electrical distribution network is undergoing tremendous modifications with the introduction of distributed generation technologies which have led to an increase in fault current levels in the distribution network. Fault current limiters have been developed as a promising technology to limit fault current levels in power systems. Though, quite a number of fault current limiters have been developed; the most common are the superconducting fault current limiters, solid-state fault current limiters, and satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The simulation parameters to test and validate the MBNSFCL are shown in Table 1. The values for the various components of the NSFCL are shown for each network guided by the equations developed by Fokui et al (2021) governing the functional principles of the FCL. The series reactor in each network is chosen to be as small as possible such that minimal current ripples are experienced in the MBNSFCL during no fault conditions.…”
Section: Simulation Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation parameters to test and validate the MBNSFCL are shown in Table 1. The values for the various components of the NSFCL are shown for each network guided by the equations developed by Fokui et al (2021) governing the functional principles of the FCL. The series reactor in each network is chosen to be as small as possible such that minimal current ripples are experienced in the MBNSFCL during no fault conditions.…”
Section: Simulation Parametersmentioning
confidence: 99%
“…This paper is an extension of a study reported in Fokui et al (2021). In that work, an MBNSFCL was designed for distribution network applications; and it was tested on a simple network that was a single-phase extraction of the IEEE 4 node test distribution network with its inline transformer removed as can be read in (Fokui et al, 2021).…”
mentioning
confidence: 99%